The Raymond Tallis Reader - Tallis, R. author. aut Link
XXX, 382 p.
Keywords: The Raymond Tallis Reader provides a comprehensive survey of the work of this passionate, perceptive and often controversial thinker. Key selections from Tallis's major works are supplemented by Michael Grant's detailed introduction and linking commentary. From nihilism to Theorrhoea, from literary theory to the role of the unconscious, The Raymond Tallis Reader guides us through the panoptic sweep of Tallis's critical insights and reveals a way of thinking for the twenty-first century.